Incidental Finding of a Homozygous p.M348K Asymptomatic Italian Patient Confirms the Many Faces of Cystic Fibrosis - Rossana Molinario; Sara Palumbo; Paola Concolino; Sandro Rocchetti; Roberta Rizza; Giovanni Luca Scaglione; Angelo Minucci; Ettore Capoluongo (Case Reports in Genetics)
Cystic fibrosis (CF; OMIM number 219700) is an autosomal recessive disease caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene, which results in abnormal viscous mucoid secretions in multiple organs and whose main clinical features are pancreatic insufficiency, chronic endobronchial infection, and male infertility. We report the case of a 47-year-old apparently normal male resulting in homozygosity for the mutation p.M348K from nonconsanguineous parents. The proband was screened using a standard panel of 70 different tested on NanoChip 400 platform. The massive parallel pyrosequencing on 454 JS machine allowed the second level analysis. The patient was firstly screened with two different platforms available in our laboratory, obtaining an ambiguous signal for the p.R347P mutation. For this reason we decided to clarify the discordant result of CFTR status by Next Generation Sequencing (NGS) using 454 Junior instrument. The patient is resulted no carrier of the p.R347P mutation, but NGS highlighted a homozygous substitution from T>A at position 1043 in the coding region, causing an amino acid substitution from methionine to lysine (p.M348K). Casual finding of p.M348K homozygote mutation in an individual, without any feature of classical or nonclassical CF form, allowed us to confirm that p.M348K is a benign rare polymorphism.